Comparison of Child Development Between Aterm and Premature Birth at Age 2-3 Years Old - Innas Tiara Ardhiani (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Objective: Premature births are at risk of developing language delays, motor balance and coordination. This study aims to analyze developmental differences in children with a history of premature birth and term. Methods: The data used was primary data through filling questionnaires and interviews to subjects. This study was observational analytic with retrospective cohort design. The population was all 2-3 years old children at Kabupaten Probolinggo. Sampling was using a simple sampling formula and obtained 100 children into 2 groups. First group was 50 children who aterm at birth. Second group was 50 children who premature at birth. Result: The result showed that there were there is significant different at child development between aterm and premature born childen (p<0.05). The relative risk (RR) analysis showed that the value is significant enough. Children development was influenced by type of born (RR=1.647x) Conclusion: The development of 2-3 years old children is very important, especially children with a history of premature birth who have a risk of developmental disorders. Parents should give more attention in providing appropriate developmental stimulation according to the child's age.